O uso do motor portátil na região de Abaetetuba: efeitos sobre o cotidiano de uma escola ribeirinha Amazônica - NEGRÃO, Dionilson Corrêa (2024)
The present study, carried out through participant observation, aims to describe a socio-technical network established after entering the islands region of Abaetetuba (riverside municipality located in the northeast of Pará) of Portable internal combustion engines, small in size and low cost, used with long tails, in the propulsion of several types of boats and their effects about the daily life of a riverside school in the Amazon. The study problematizes the consequent adaptive actions that modify/modified the relationships previously established by riverine people with nature, geographic space, the forms of production and social relations and school life, influenced by then by the popularization of motorized propulsion on a large scale that ended up for establishing the engine and parts stores, creating manpower in certain shipyards, gas stations as a mandatory crossing point in the new network. To carry out this work, a survey with employees was used. of a riverside school with the application of semi-structured interviews, which enabled its development. The study allows us to conclude that if established new relationships of students, teachers and managers, with the environment and culture from the introduction of this sociotechnical artifact in the riverside community.